Problem Analysis of Elementary School Children as Planning Assesment Program Guidance and Counseling - Muhammad Chamdani (Universitas Sebelas Maret, 2019)
The research is based on an analysis of the problems of elementary school children and efforts to develop planning and counseling programs. This type of quantitative research with survey sampling techniques. The research location was in the elementary school in Klirong sub-district, Kebumen. Data collection techniques using observation, interviews, and documentation methods. The results showed that there were several types of problems of elementary school children so that there was a need for planning counseling and programs to help elementary students optimal development.